Modern Approaches to Dispute Resolution: Ad Hoc and Institutional Mediation in Asia and Africa - Yusuf Gunawan (IBLAM LAW REVIEW, 2026)
Ad hoc and private institutional mediation are two forms of modern approaches to dispute resolution that are increasingly developing in Asia and Africa. These two approaches offer effective alternatives to conventional litigation systems with the advantages of flexibility, time efficiency, and lower costs. Ad hoc mediation gives the parties the freedom to appoint a mediator without being tied to a particular institution, while private institutional mediation provides a structured and professional framework through a credible mediation institution. In Asia, the success of institutional mediation is driven by supportive regulations and increased mediator capacity, with dispute resolution rates between 40% and 70%. In Africa, the integration of mediation with local wisdom and indigenous cultures increases the success rate of mediation to 50% to 65%. The implementation of these two approaches within a progressive legal framework shows that ad hoc and private institutional mediation not only reduce the burden on the judicial system but also improve access to justice in a more equitable and civilized manner. These approaches represent the evolution of harmonious and equitable dispute resolution in Asia and Africa, providing strategic solutions to current and future legal challenges.